지역 병원에서의 위암의 시기적 변화 양상 - 정인목(In Mok Jung); 공성호(Seong Ho Kong); 서준석(Jun Suk Suh); 김영철(Young Chul Kim); 허승철(Seung Chul Heo); 안영준(Young Joon Ahn); 김수진(Soo-Jin Kim); 권오중(Oh Joong Kwon); 정중기(Jung Kee Chung) (Annals of surgical treatment and research, 2004)
KCI Citation Count: 2